Platelet SHARPIN regulates platelet adhesion and inflammatory responses through associations with alpha IIb beta 3 and LUBAC - Kasirer-Friede Ana; Peuhu Emilia; Ivaska Johanna; Shattil Sanford J (American Society of Hematology, 2022)
Platelets form hemostatic plugs to prevent blood loss, and they modulate immunity and inflammation in several ways. A key event during hemostasis is activation of integrin αIIbβ3 through direct interactions of the β3 cytoplasmic tail with talin and kindlin-3. Recently, we showed that human platelets express the adapter molecule Shank-associated RH domain interacting protein (SHARPIN), which can associate directly with the αIIb cytoplasmic tail and separately promote NF-κB pathway activation as a member of the Met-1 linear ubiquitination activation complex (LUBAC). Here we investigated the role of SHARPIN in platelets after crossing Sharpin flox/flox (fl/fl) mice with PF4-Cre or GPIbα-Cre mice to selectively delete SHARPIN in platelets. SHARPIN-null platelets adhered to immobilized fibrinogen through αIIbβ3, and they spread more extensively than littermate control platelets in a manner dependent on feedback stimulation by platelet adenosine diphosphate (ADP) (P < .01). SHARPIN-null platelets showed increased colocalization of αIIbβ3 with talin as assessed by super-resolution microscopy and increased binding of soluble fibrinogen in response to submaximal concentrations of ADP (P < .05). However, mice with SHARPIN-null platelets showed compromised thrombus growth on collagen and slightly prolonged tail bleeding times. Platelets lacking SHARPIN also showed reduced NF-κB activation and linear ubiquitination of protein substrates upon challenge with classic platelet agonists. Furthermore, the loss of platelet SHARPIN resulted in significant reduction in inflammation in murine models of colitis and peritonitis (P < .01). Thus, SHARPIN plays differential and context-dependent roles in platelets to regulate important inflammatory and integrin adhesive functions of these anucleate cells.